HUBUNGAN KOORDINASI MATA DAN TANGAN DENGAN HASIL SHOOTING FREE THROW PADA TIM BOLA BASKET PUTRA SMA NEGERI 5 PEKANBARU - Prihantoro, Dwi Des; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem in this study is a minimize of performance ability in free throw shooting. This is presumally because the lack of hand-eye coordination, the relationship between hand-eye coordination with the free throw shooting in the male basketball team at SMA N 5 Pekanbaru. The sample in this study is the Male Basketball team at SMAN 5 Pekanbaru which consisted 12 people. A sampling technique was overall population (total sampling). The instruments used in this research is to test hand-eye coordination which aims to measure the eye-hand coordination skills test set shoot with the free throw shooting that aimed to measure skills penalty shot. After that, the data was processed statistically with lilifors test at significant level 0,05α. The hypothesis is there is significant relationship between eye-hand coordination with the results free throw in a game of basketball. Based on analysis of test lilifors produce L count (x) of 0.190 and 0.242 tables L, L count (y) amounted to 0,084 and 0,242 L table, meaning L count <L table, then the samples came from normal populations. From the calculation of product moment correlation between eye and hand coordination gained the results of free throw shooting where r arithmetic (-0.142) <r table (0.602) therefore Ha is rejected and Ho is accepted. Thus there are no significant relationship between eye-hand coordination withthe shooting male basketball team at SMAN N 5 Pekanbaru. In summary insignificant correlation does not always mean there is no relationship, although the relationship is very low or weak.Key Words: Hand-Eye Coordination With The Result Free Throw.